2019
DOI: 10.12962/j23546026.y2019i1.5106
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Savonius Wind Turbine with Fluid-Rotor Interactions

Abstract: Previous numerical studies in the Savonius wind turbine mostly used constant angular velocity as input data, where the values were obtained from experiments. This process cannot be used in the design optimization of the turbine, in which the angular velocity of the modified turbine is not known a priority. In numerical simulation, the use of loading system to get constant angular velocity to control the tip speed ratio (TSR), tends to have fluctuating value on output data. Moreover, the values of angular veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The use of the endplate significantly affects the performance of the Savonius turbine. Previous research studies have shown a comparison of the numerical streamline of a Savonius turbine with and without an endplate with 3-dimensional visualization [15]. The results showed that the Savonius turbine without endplate has a significant enough resistance in the downstream turbine.…”
Section: Introductionmentioning
confidence: 96%
“…The use of the endplate significantly affects the performance of the Savonius turbine. Previous research studies have shown a comparison of the numerical streamline of a Savonius turbine with and without an endplate with 3-dimensional visualization [15]. The results showed that the Savonius turbine without endplate has a significant enough resistance in the downstream turbine.…”
Section: Introductionmentioning
confidence: 96%
“…Until now, the utilization of wind turbines in Indonesia has not been carried out on a large scale. Some turbines that are widely applied in Indonesia include propeller turbines [3], Turgo [4], Crossflow [5], Pelton [6], and Savonius [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbines are one of the tools used in energy utilization, especially the use of wind energy which is often used as one of the power plants, because the use of wind energy is one of the natural resources that will not run out [1]. The classification of wind turbines based on their axes is classified into 2 types, namely horizontal and vertical axes [2]. Wind turbine performance can be improved by varying the shape of turbine blades such as overlap [3], myring, and fin [4]- [7] or variations on the addition of a disruptive cylinder [8], [9].…”
mentioning
confidence: 99%